Pengaruh Penggunaan Media Audio Visual Terhadap Hasil Belajar Menulis Teks Berita Siswa Kelas XI SMA Negeri 1 Gowa - Muin, Hajrawati; Baharman; Ni Nengan Wirjani (Study Program of Indonesian Language Education, Faculty of Languages and Literature, Universitas Negeri Makassar, 2024)
The purpose of this study was to describe the effect of using audio-visual media on the learning outcomes of writing news texts of Class XI SMA Negeri 1 Gowa students. The method used in this research is pre-experiment with quantitative approach. Data collection techniques using written tests with descriptive and inferential data analysis techniques. The results of this study showed that students' learning outcomes before using audio visual media obtained an average score of 51.50. Student learning outcomes after using audio visual media obtained an average score of 78.70. The use of audio visual media can be concluded to have an influence in improving the learning outcomes of students in class XI SMA Negeri 1.